Il12a Deletion Aggravates Sepsis-Induced Cardiac Dysfunction by Regulating Macrophage Polarization - Zhen Wang; Zhen Wang; Zhen Wang; Menglin Liu; Di Ye; Di Ye; Di Ye; Jing Ye; Jing Ye; Jing Ye; Menglong Wang; Menglong Wang; et al. (Frontiers Media S.A., 2021)
Cardiac dysfunction is a well-recognized complication of sepsis and is associated with the outcome and prognosis of septic patients. Evidence suggests that Il12a participates in the regulation of various cardiovascular diseases, including heart failure, hypertension and acute myocardial infarction. However, the effects of Il12a in sepsis-induced cardiac dysfunction remain unknown. In our study, lipopolysaccharide (LPS) and cecal ligation and puncture (CLP) model were used to mimic sepsis, and cardiac Il12a expression was assessed. In addition, Il12a knockout mice were used to detect the role of Il12a in sepsis-related cardiac dysfunction. We observed for the first time that Il12a expression is upregulated in mice after LPS treatment and macrophages were the main sources of Il12a. In addition, our findings demonstrated that Il12a deletion aggravates LPS-induced cardiac dysfunction and injury, as evidenced by the increased serum and cardiac levels of lactate dehydrogenase (LDH) and cardiac creatine kinase-myocardial band (CK-MB). Moreover, Il12a deletion enhances LPS-induced macrophage accumulation and drives macrophages toward the M1 phenotype in LPS-treated mice. Il12a deletion also downregulated the activity of AMP-activated protein kinase (AMPK) but increased the phosphorylation levels of p65 (p-p65) and NF-κB inhibitor alpha (p-IκBα). In addition, Il12a deletion aggravates CLP-induced cardiac dysfunction and injury. Treatment with the AMPK activator AICAR abolishes the deterioration effect of Il12a deletion on LPS-induced cardiac dysfunction. In conclusion, Il12a deletion aggravated LPS-induced cardiac dysfunction and injury by exacerbating the imbalance of M1 and M2 macrophages. Our data provide evidence that Il12a may represent an attractive target for sepsis-induced cardiac dysfunction.